CLINICAL OBSERVATION: CONGENITAL CYSTIC ADENOMATOUS LUNG MALFORMATION IN A NEWBORN - Татьяна Михайловна Черкасова; Анастасия Борисовна Казанина; Елена Станиславовна Кравцова; Софья Станиславовна Столярова; Светлана Николаевна Дуплик; Ксения Давыдовна Видершпан (Мать и дитя в Кузбассе)
The clinical case of an extensive congenital cystic adenomatous lung malformation type I in a newborn is represented by typical diagnostic findings, but with a feature of clinical manifestations. After birth, the child's condition worsened due to an increase in respiratory and cardiovascular insufficiency. Instrumental diagnostic methods revealed a gigantic cyst of the lower lobe of the left lung. The cyst increased in size by almost 2 times, preventing the straightening of the left lung, the right lung was compressed, the median shadow was shifted to the right – signs of pronounced intrathoracic pressure and pulmonary hypertension were revealed. It was recommended to refrain from surgical treatment until the stabilization of the respiratory and cardiovascular disorders. A huge cyst of the lower lobe of the left lung was drained. Respiratory and cardiovascular disorders are compensated in dynamics. The right lung was straightened out and after that surgical treatment was performed.